An Overview of D7 Protein Structure and Physiological Roles in Blood-Feeding Nematocera - Patricia H. Alvarenga; John F. Andersen (Biology, 2022)
Each time an insect bites a vertebrate host, skin and vascular injury caused by piercing triggers a series of responses including hemostasis, inflammation and immunity. In place, this set of redundant and interconnected responses would ultimately cause blood coagulation, itching and pain leading to host awareness, resulting in feeding interruption in the best-case scenario. Nevertheless, hematophagous arthropod saliva contains a complex cocktail of molecules that are crucial to the success of blood-feeding. Among important protein families described so far in the saliva of blood sucking arthropods, is the D7, abundantly expressed in blood feeding Nematocera. D7 proteins are distantly related to insect Odorant-Binding Proteins (OBP), and despite low sequence identity, observation of structural similarity led to the suggestion that like OBPs, they should bind/sequester small hydrophobic compounds. Members belonging to this family are divided in short forms and long forms, containing one or two OBP-like domains, respectively. Here, we provide a review of D7 proteins structure and function, discussing how gene duplication and some modifications in their OBP-like domains during the course of evolution lead to gain and loss of function among different hematophagous Diptera species.